THE DEPICTION OF INDIA IN "BABURNAMA" - Tursunbaeva Minavvarkhan Bahromjon daughter (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2025)
Baburnama, written by Zahiriddin Muhammad Babur, is one of the most important historical-biographical sources of its time. In this work, Babur provides detailed descriptions of the regions he conquered, particularly India. He offers valuable information about India’s natural geography, climate, the lifestyle of its inhabitants, culture, traditions, and political environment. This article deeply analyzes the depiction of India in Baburnama and compares it with modern historical research.